A 2D finite element procedure for magnetic field analysis taking into account a vector Preisach model. Issue 3 (1997) - Dupré Dupré, Luc R. Luc R.; Van Keer Van Keer, Roger Roger; Melkebeek Melkebeek, Jan A. A. Jan A. A.
Abstract : The main purpose of this paper is to incorporate a refined hysteresis model, viz. a vector Preisach model, in 2D magnetic field computations. To this end the governing Maxwell equations are rewritten in a suitable way, which allows to take into account the proper magnetic material parameters and, moreover, to pass to a variational formulation. The variational problem is solved numerically by a FE approximation, using a quadratic mesh, followed by the time discretisation based upon a modified Cranck Nicholson algorithm. The latter includes a suitable iteration procedure to deal with the nonlinear hysteresis behaviour. Finally, the effectiveness of the presented mathematical tool has been confirmed by several numerical experiments.